Οι υστεροβυζαντινές τοιχογραφίες δύο σχετικά άγνωστων μνημείων των Αχαρνών (Μενίδι). Η απόδοσή τους σε γνωστό ζωγραφικό εργαστήριο της Αττικής. - ΑΒΡΑΜΙΔΗΣ Βασίλειος (Byzantina Symmeikta, 2024)
During mural maintenance works in Agios Ioannis Prodromos "Fasting" in Menidi and Agios Nikolaos in Varympompi, phases of late Byzantine decoration were revealed. Until then, the two churches dated to post Byzantine period. In the present study, the late Byzantine decoration of the monuments is thoroughly examined. Through comparisons with mural ensembles of churches in the wider area, we attempt to render it in a well-known local painting workshop, with precisely dated works in the fourth decade of the 13th century. The high quality of the examined decoration under consideration, in the context of Latin-occupied Attica, demonstrates the importance of the late Byzantine settlement of Menidi for the wider area of the N-NE Athenian field.